KONTRIBUSI PERMAINAN HITAM HIJAU TERHADAP KETERAMPILAN LARI SPRIN MURID SMP NEGARI 11 KOTA JAMBI - Ilham Ilham; Arsil Arsil; Muhammad Ali (Publikasi Pendidikan, 2015)
Generally this research is for knowing the contribution of hitam hijau and sentuh batu games on the ability to sprints for female student of SMPN 11 jambi, specificially this research is for knowing : (1) the contribution of hitam hijau games on the ability to sprints. (2) the contribution of sentuh batu games on the ability to sprints. (3) differences in the contribution of hitam hijau and sentuh batu games on the ability to sprint. And the advantage of this research are (1) for the physical education teacher is as the information form of the game that can be used as a learning media  in order to achieve the indicator skills to run sprints . (2) For the trainers, is for building the ability to sprint for athlete can be done with the hitam hijau and sentuh batu games. The research method that used in this research is the experimental method, using the two groups pretest post test design. The variable in this research is the ability to sprint as the binding variable and the hitam hijau and sentuh batu games as  the free variable . The data that we collected were analyzed with the t test, but before that we conducted the normality and homogenity test. The hypothesis testing result are (1) t hitung (9,35) > t table (1,69). (2) t hitung (6,44) > t table (1,69). (3) t hitung (4,54) > t tabel (2,24).  Thus it can be concluded that (1) hitam hijau games gives the significant contribution for the ability to sprint. (2) sentuh batu games gives the significant contribution for the ability to sprint. (3) there are significant differences  in the contribution of hitam hijau and sentuh batu games for the ability to sprint. Hitam hijau game is far better than sentuh batu games.Keywords : Hitam hijau, Sentuh batu, The ability to sprint